Antibacterial Effectiveness of Yellow Turmeric (Curcuma longa) and White Turmeric (Curcuma zedoaria) Extracts against Aeromonas salmonicida: Antibacterial Effectiveness of Yellow Turmeric (Curcuma longa) and White Turmeric (Curcuma zedoaria) Extracts against Aeromonas salmonicida - Nisa Hakimah; Budi Rianto Wahidi; Tri Ari Setyastuti; Anja Asmarany; Era Insivitawati; Budi Sugianti; Dewi Nurmalita Suseno; Shara Jayanti (Department of Aquaculture, 2026)
Aeromonas salmonicida is a major fish pathogenic bacterium responsible for significant losses in aquaculture. The growing concern over antibiotic resistance has driven interest in plant-based antibacterial alternatives. This study examined the extraction yield, phytochemical characteristics, and in vitro antibacterial activity of ethanolic extracts obtained from the rhizomes of Curcuma longa and Curcuma zedoaria against Aeromonas salmonicida. Extraction was conducted using an ethanol-based maceration technique. Qualitative phytochemical screening was subsequently performed, and antibacterial activity was evaluated through the disc diffusion assay at extract concentrations ranging from 10% to 100%. The results showed that C. longa produced a higher extraction yield (7.18%) than C. zedoaria (3.19%). Both extracts contained flavonoids, total phenolics, alkaloids, and tannins, while saponins were not detected. Antibacterial activity against A. salmonicida increased with extract concentration, reaching maximum inhibition at 100%, with zone diameters of 12.97 ± 0.57 mm (C. longa) and 12.17 ± 0.61 mm (C. zedoaria). Significant differences were observed among concentration treatments. In conclusion, ethanolic extracts of Curcuma longa and Curcuma zedoaria demonstrate promising plant-based antibacterial activity against A. salmonicida in vitro, supporting their potential use in aquaculture health management. Nevertheless, further in vivo studies and toxicity evaluations are required before practical application.